Use of ring recoveries to predict habitat suitability in small passerines - Tellería, José (2012)
Aim Abundance of small passerines may be distributed over large wintering areas according to geographical patterns that are difficult to detect. This may prevent the identification and conservation of the most suitable sectors, or the detection of local and regional features affecting the species during winter. In this paper, we explore the usefulness of ring recoveries to predict bird distribution in wintering grounds by using Maxent, one of the presence-only techniques available for modelling species distributions. We test whether suitability indices obtained in 2.5×2.5km UTM squares from ring recoveries were positively correlated with the actual abundance of robins (Erithacus rubecula) and blackcaps (Sylvia atricapilla) inside the squares. Location Spain. Methods We used 686 and 1139 localities across the country in which blackcap and robin ring recoveries were recorded by the Spanish Office of Migratory Species to generate the suitability maps. In addition, we sampled bird abundance inside 70 control squares independent of ring recovery localities along a belt crossing mountains, highlands and lowlands of the Iberian Peninsula during January from 2006 to 2011. Results Suitability indices predicted by Maxent were positively correlated with robin (r=0.42, n=70, P<0.001) and blackcap (r=0.52, n=70, P<0.001) abundances in the 70 control squares along the belt crossing the Iberian Peninsula. Main conclusions These results suggest that the use of distribution models with ring recoveries may be used to describe the habitat suitability of the winter ranges of small, common passerines. This also means that the huge number of ring recoveries stored in national and transnational data banks could be used to explore the factors shaping bird ranges and to forecast the geographical distribution of suitable wintering areas of migratory birds in large, poorly known regions. This may be useful in biogeography and conservation. © 2012 Blackwell Publishing Ltd.